Architectural Frontiers: Drawing on the Capacity to Endure Cognitive Tension - Kim Tanzer (Oz, 1995)
The phenomenon of widespread anxiety is not new; despite their historical distance and disciplinary diversity, each citation above echoes the anxieties underlying today's popular and professional concerns. The Lynds' study of Middletown captures the pervasive anxiety felt by members of modern society in transition, while Hitchcock and Johnson demonstrate the parallel urge felt by architects to erase such anxieties through formal hegemony.